Movement Skills in Foot Ball Games for Grade 7 and 8 of SMP Negeri 3 Kayu Agung - Hamid, Sarwan; Lian, Bukman; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the comparison of movement skills in football games in 7th and 8th grade students at SMP Negeri 3 KayuAgung, Ogan Komering Ilir Regency. The research method is defined as a scientific way to obtain data with specific purposes and uses. This research is quantitative descriptive research, namely research by giving tests to students, so that the results of motion abilities in football games are obtained and analyzed. The results during the author’s observation of the problem obtained that the ability to move in the game of soccer in students of SMP Negeri 3 Kayu Agung is still very lacking. The phenomenon that occurs is that there are several students who have not been able to perform soccer game movements. Especially in grade 7 and grade 8 students of SMP Negeri 3 Kayu Agung. Related to this problem, the solution is to emphasize more movement skills in soccer games so that these abilities can improve properly.